The WE-ARe model’s potential to enhance digital literacy of preservice biology teachers - Astuti Muh Amin; Fitriyah Karmila; Zainal A. Laode; E. Ermin; Adjar Yusrandi Akbar; Mulkah Adebisi Ahmed (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
In the era of globalization, digital literacy has become one of the competencies that students must possess. Rarely can one find research that examines the effect of the WE-ARe model on digital literacy in biology education. WE-ARe is a constructivist-based active learning model consisting of Warm-up, Exploring, Argumentation, and Resume phases that emphasize students’ collaborative and elaborative qualities. The objective of the study was to determine the impact of the WE-ARe model on the digital literacy of future biology teacher candidates. This is a quasi-experimental study using the Pretest-Posttest Control Group Design. The research population comprised all Tadris Biology students from IAIN Ternate and STKIP Kie Raha in the City of Ternate, North Maluku, Indonesia. The research sample contained 60 fourth-semester students from the Department of Tadris Biology. The validity score for the literacy digital instrument was 3.89 (very valid), while the correlation value (r-calculated) was 0.585. The Cronbach-Alpha analysis showed a score of 0.939, indicating that the literacy digital instrument was valid and reliable for use in data collection. This study was conducted during the even semester of the 2021/2022 academic year. The data were analyzed through ANACOVA using 5% level of significance. The results demonstrated that the WE-ARe model had an impact on the preservice biology teachers’ digital literacy. The findings of this study provide an insight on the use of a new learning model that can be used to enhance students’ 21st century skills.